Economic Empowerment of Low-Income Households through Financial Literacy and Entrepreneurial Education in Tebing Tinggi, Parapat, and Medan - Andi; Muammar Rinaldi (Outline Publisher, 2024)
The problem of poverty is an issue that continues to be a major concern in Indonesia, including in North Sumatra Province. This research aims to identify the socio-economic characteristics of poor households in North Sumatra Province in 2024, taking into account factors such as income, home ownership, age, number of family members, education, and access to financial institutions. The research method used is qualitative with a descriptive approach, involving analysis of primary data in the form of interviews and secondary data from related literature. The results of the analysis show that the majority of households in the area face serious economic challenges, with low incomes and large family members. The solution to overcome this problem is through collaboration between government, the private sector, and non-government organizations, with a focus on increasing access to education services, health, social assistance programs, skills training, and job creation. It is hoped that this joint effort can reduce the level of poverty in North Sumatra Province, providing opportunities for a more decent and sustainable life for the community.